Resilience of Inmates of Class IIA Pekalongan State Prison in Facing Legal Problems - Triono, Yuli; Dzil Kamalah, Aisyah (NHM PRESS, 2025)
Prolonged changes in environment and more difficult situations than before can damage psychological conditions and even lead to thoughts of ending one's life prisoners. resilience, which is the effort to bounce back and improve the difficult situation faced. The study aims to evaluate how the resilience of prisoners in the Class IIA State Detention Center Pekalongan in facing legal problems is depicted. This study uses a descriptive method with a cross-sectional design. Data collection was carried out using a simple random sampling technique. The sample in this study was 155 prisoners of the Class IIA state detention center in Pekalongan. The respondents' resilience level was measured using the Resilience Scale. Based on the resilen respondents showing high resilience were 81 people (54.3%). It is suggested for future researchers to conduct research in two or three locations for data collection so that the data obtained is more varied and meets the required sample size